Podstawa woda w antroponimii polskiej - Breza, Edward (Nazwy terenowe i miejscowe w przestrzeni fizycznej, 2016)
The author studies Polish and (as far as the sources were available) Indo–European forenames and surnames that are derived from the root word woda ‘water’: among the forenames the author has found only the Latin nickname (cognomen) Aquensis, derivate of an adjective aquensis, -is, -e ‘connected with water’: aqua, -ae ‘water’. Contemporary Polish surnames derived from the root word woda ‘water’ have been written out from Słownik nazwisk współcześnie w Polsce używanych [The Dictionary of Surnames Contemporarily Used in Poland], vol. I–X published by Kazimierz Rymut (Kraków 1992–1994) and from Middle Polish period (16th–18th century) from regional surname studies by different authors. In Pomeranian region in Old Polish period (until the end of 15th century) none of the surnames of interest were confirmed, there were also few in Middle Polish period. Relatively many surnames are derived from Upper German noun Wasser and its Lower German equivalent Wader or Water. The written out surnames are presented in derivation lines such as: Woda > Wodak > Wodacki. In the study there are: 1) surnames with double motivation, e.g. Wodan from the name of the main German god or from common noun Woda with suffix -an; 2) compound word e.g. Koliwoda, Paliwoda, Woziwoda, that may be derived from old common nouns (appellatives) paliwoda ‘a very reckless man, a madcap’, woziwoda ‘someone who supplied water to the residents’.